The evolution of the Molopo drainage - Bootsman, Cornelis Siebe (My University, 2016)
The appearance of the dry Molopo River with its generally wide and shallow valley cut into the Kalahari Group sediments, but more especially its few impressive rock-cut gorges, has intrigued many people over the ages, and led to many theories concerning its history. The rock-cut gorges, in particular, have traditionally been attributed to ancient, previously much more extended drainage lines, more or less in the same geographical position as the present Molopo Valley. An analysis of the sediment body of the Kalahari Group, and both, alluvial gravels and geomorphic features on the rim of the Cainozoic Kalahari Basin, have indicated that the Molopo drainage has gradually shifted westward over time, in response to a tilting of the drainage area, which lies across the south-eastern rim of the Kalahari Basin, The present geographical position of the Molopo River is thus a relatively recent one in its evolution. The earliest traces of drainage lines in the area predate the Permo-Carboniferous glaciation of Gondwana. A preglaciation valley system with only some similarities to the present-one flowed in a northwesterly direction. There is a long hiatus in the evidence from the end of the glaciation to the beginning of the formation of the Calnozoic Kalahari Basin. The most significant feature of that intermediate period, is a large meteorite impact which occurred near Morokweng at the J-K boundary. The Cainozoic evolution of the Molopo drainage has been strongly influenced by both tectonics and climatic change. Tectonics, which include both the initial formation of the Kalahari Basin and Neogene warpings of the intra-continental axes of uplift, caused the interruption of a pre- Kalahari southward flowing drainage system, an extended upper Molopo, the existence of the Molopo as an endoreic system for an extended period of time, and a westward shift of the entire Molopo drainage system. Progressively more arid conditions interrupted by humid climatic pulses of decreasing intensity have occurred since the Cretaceous. The aridifying conditions caused the existence of playa-like conditions over long periods oftime in the back-tilted section of the proto-Molopo. This was followed by a rapid sediment infilling of the sub-basin and a major rejuvenation phase, which caused the incision of the Molopo River into the duricrusted sediments of the Kalahari Group, and the re-establishment of the Molopo River as an exoreic drainage system in its present position. Rock-cut terrace remnants in the upper Molopo give evidence of much smaller climatic changes during the Quaternary. There has been no integrated flow in living memory.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 1998
Keywords: Watersheds -- South Africa.; Geomorphology -- South Africa.